An Electrochemical Study of the Oxidation of Hydrogen at Platinum Electrodes in Several Room Temperature Ionic Liquids - Silvester, Debbie; Aldous, L.; Hardacre, C.; Compton, R. (American Chemical Society, 2007)
The electrochemical oxidation of dissolved hydrogen gas has been studied in a range of room-temperature ionic liquids (RTILs), namely [C2mim][NTf2], [C4mim][NTf2], [N6,2,2,2][NTf2], [P14,6,6,6][NTf2], [C4mpyrr]- [NTf2], [C4mim][BF4], [C4mim][PF6], [C4mim][OTf], and [C6mim]Cl on a platinum microdisk electrode of diameter 10 ím. In all cases, except [C6mim]Cl, a broad quasi-electrochemically reversible oxidation peak between 0.3 to 1.3 V vs Ag was seen prior to electrode activation ([C6mim]Cl showed an almost irreversible wave). When the electrode was pre-anodized (“activated”) at 2.0 V vs Ag for 1 min, the peak separations became smaller, and the peak shape became more electrochemically reversible. It is thought that the electrogenerated protons chemically combine with the anions (A-) of the RTIL. The appearance and position of the reverse (reduction) peak on the voltammograms is thought to depend on three factors: (1) the stability of the protonated anion, HA, (2) the position of equilibrium of the protonation reaction HA h H+ + A- , and (3) any follow-up chemistry, e.g., dissociation or reaction of the protonated anion, HA. This is discussed for the five different anions studied. The reduction of HNTf2 was also studied in two [NTf2]--based RTILs and was compared to the oxidation waves from hydrogen. The results have implications for the defining of pKa in RTIL media, for the development of suitable reference electrodes for use in RTILs, and in the possible amperometric sensing of H2 gas.